Noncoding RNAs as an emerging resistance mechanism to immunotherapies in cancer: basic evidence and therapeutic implications - Wang, Man; Yu, Fei; Li, Peifeng (Frontiers in Immunology, 2023)
The increasing knowledge in the field of oncoimmunology has led to extensive research into tumor immune landscape and a plethora of clinical immunotherapy trials in cancer patients. Immunotherapy has become a clinically beneficial alternative to traditional treatments by enhancing the power of the host immune system against cancer. However, it only works for a minority of cancers. Drug resistance continues to be a major obstacle to the success of immunotherapy in cancer. A fundamental understanding of the detailed mechanisms underlying immunotherapy resistance in cancer patients will provide new potential directions for further investigations of cancer treatment. Noncoding RNAs (ncRNAs) are tightly linked with cancer initiation and development due to their critical roles in gene expression and epigenetic modulation. The clear appreciation of the role of ncRNAs in tumor immunity has opened new frontiers in cancer research and therapy. Furthermore, ncRNAs are increasingly acknowledged as a key factor influencing immunotherapeutic treatment outcomes. Here, we review the available evidence on the roles of ncRNAs in immunotherapy resistance, with an emphasis on the associated mechanisms behind ncRNA-mediated immune resistance. The clinical implications of immune-related ncRNAs are also discussed, shedding light on the potential ncRNA-based therapies to overcome the resistance to immunotherapy.